Annexin A7 mediates lysosome repair independently of ESCRT-III - Ebstrup, Malene Laage; Sønder, Stine Lauritzen; Fogde, Ditte Louise; Heitmann, Anne Sofie Busk; Dietrich, Tiina Naumanen; Dias, Catarina; Jäättelä, Marja; Maeda, Kenji; Nylandsted, Jesper (Frontiers in Cell and Developmental Biology, 2024)
Lysosomes are crucial organelles essential for various cellular processes, and any damage to them can severely compromise cell viability. This study uncovers a previously unrecognized function of the calcium- and phospholipid-binding protein Annexin A7 in lysosome repair, which operates inde-pendently of the Endosomal Sorting Complex Required for Transport (ESCRT) machinery. Our re-search reveals that Annexin A7 plays a role in repairing damaged lysosomes, different from its role in repairing the plasma membrane, where it facilitates repair through the recruitment of ESCRT-III components. Notably, our findings strongly suggest that Annexin A7, like the ESCRT machinery, is dispensable for membrane contact site formation within the newly discovered phosphoinositide-initiated membrane tethering and lipid transport (PITT) pathway. Instead, we speculate that Annexin A7 is recruited to damaged lysosomes and promotes repair through its membrane curvature and cross-linking capabilities. Our findings provide new insights into the diverse mechanisms underlying lyso-somal membrane repair and highlight the multifunctional role of Annexin A7 in membrane repair.